Pengaruh Persepsi Harga Dan Promosi Online Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variable Moderasi (Survey Pada Konsumen CS Used Cabang Cirebon) - JAJA JAKARIA; Lili Karmelia Fitriani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Research objectives: 1) understand the effect of perceived price on purchasing decisions. 2) understand the influence of online promotions on purchasing decisions. 3) understand the effect of brand image on purchasing decisions. 4) understand whether brand image moderates the effect of perceived price on purchasing decisions. 5) understand whether brand image moderates the effect of online promotions on purchasing decisions. The population in this study were consumers of BCA Finance CS used cars at the Cirebon branch as of October 2022, with a total of 1,571 consumers. The effect of sampling the Respondents in this study were adjusted to 100 consumers. The data analysis technique in this study uses SEM analysis through the SmartPLS application. The results of the study are 1) price perceptions have a significant positive effect on purchasing decisions. 2) online promotions have no effect on purchasing decisions. 3) brand image has a significant positive effect on purchasing decisions. 4) brand image cannot moderate the effect of perceived price on purchasing decisions. 5) brand image cannot moderate the effect of online promotions on purchasing decisions. Keywords : Purchase Decision; Price Perception; Online Promotion; Brand Image